IMPLEMENTASI PERATURAN MENTERI DALAM NEGERI NO. 38 TAHUN 2018 DALAM PENYUSUNAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) TAHUN ANGGARAN 2019 (Studi Kasus di Badan Pendapatan, Pengelolaan Keuangan, dan Aset Daerah/BPPKAD Kabupaten Ponorogo Tahun 2020) - Kurniawan, Alif (JI@P, 2020)
Talking about regional financial management policies cannot be separated from the policy of decentralization and regional autonomy, whereas in reality there are still many problems found in the process of preparing the Regional Government Budget in Ponorogo District each year.This research aims to describe and analyze how the implementation of Minister of Home Affairs Regulation No. 38 of 2018 in the preparation of the Regional Budget of the 2019 Budget Year along with what are the obstacles and supporters of its implementation. This type of research in research uses qualitative research using theories from Mazmanian and Sebastiar as a basis for thinking in reviewing policy implementation that is influenced by 3 main variables namely the characteristics of the problem, the characteristics of the policy and the characteristics outside the policy. The method of data collection is done by observation, interviews, and documentation. The results showed that in the implementation of the Minister of Home Affairs Regulation No. 38 of 2018, it is known that the inhibiting factors are political factors, factors of the central government, factors of limited funds / funding, as well as Programmer